The Influence of Social Media and Financial Education on Investment Interest with Investment Promotion as a Mediation Variable - Ernasari, Desi; Suhardi, Suhardi; Firdaus, Rahmad (Economic: Journal Economic and Business, 2025)
This study analyzes the influence of social media and financial education on investment interest among young people, with investment promotion as a mediating variable. Using a quantitative approach and path analysis, data were obtained from 180 respondents aged 17–30 years in the Bangka Belitung Islands Province. The results showed that financial education had a significant effect on investment promotion and investment interest. Social media had a significant effect on investment promotion, but not directly on investment interest. Investment promotion also did not significantly mediate the relationship between social media and investment interest. These findings emphasize the importance of financial education as a major factor in increasing investment interest among the younger generation in the digital era. The practical implication is the need for integration between digital marketing communication strategies and sustainable financial literacy programs. Further research is recommended to explore moderating variables such as trust in financial institutions and digital literacy for a deeper understanding of investment behavior among the younger generation.